Effectiveness of training program by blended learning on knowledge and practices regarding first aid among preparatory year engineering students at Assiut University: 10.55131/jphd/2023/210221 - Aljawfi, Adel; Hassanen , Rabaa; Sharkawy , Soad (Journal of Public Health and Development, 2023)
First aid training is necessary for engineering students to increase their health and safety knowledge relating to reducing damage and suffering and improving their chances of survival. Objective: This study aims to evaluate the effectiveness of a training program by blended learning on knowledge and practices regarding first aid among preparatory year engineering students at Assiut University. A pretest, posttest design was used in this study. About 85 participants were selected randomly from the preparatory year of engineering students at Assiut University. Participants were randomly selected and provided with a first-aid training program. Data were collected via a self-administered knowledge questionnaire sheet and an observational checklist pre, post, and three months after the program intervention. The repeated measured ANOVA was used. Results: The study revealed that 61.2% of students had poor knowledge scores about first aid in the pre-test with a total mean of 65.16±24.41, which improved to 95.3% of students who had good knowledge scores in the post-test with a total mean of 121.89±10.27, and slightly declined to 77.6% having good knowledge scores in the follow-up test with a total mean of 110.93±27.38. Moreover, 85.9% of students had poor practice scores about first aid in the pre-test with a total mean of 19.19±4.71, which improved to 72.9% having good practice scores in the post-test with a total mean of 52.49±7.84, and 65.9% having good practices scores in the follow-up test with a total mean of 48.64±13.49. The study concluded that the training program by blended learning showed a positive effect on knowledge and practices of students at post and follow-up tests. This provides a safe learning environment for engineering students. Recommendation: Blended learning programs should be taken as a learning approach in the health training program implementation.